MAP SERVER FOR VISUALIZING AIR TRAFFIC BASED ON DATA FROM A REMOTE PSEUDO RADAR - AMARA, Rafik; BELAROUSSI, Asma; BESKRI, Youcef; AISSA, Mostefa BELHADJ (MATTER: International Journal of Science and Technology, 2019)
In order to ensure the safety of aircraft operating in airspace, air traffic controllers apply a number of rules recommended by the ICAO, known as "separation rules". Previously using essentially the calculation of the estimates, they are based today on the visualization of the traffic through Air Traffic Management Systems. Traffic data comes from several sources. These include radar data from Air Traffic Control Radars. The objective of this work is to simulate, using a web map server, the evolution of air traffic: positions and flight levels of aircraft over time based on radar data. For this we use three parts. The first part, the pseudo radar, is a remote radar data server that, depending on the time, sends the data to the map server that is the second part. The latter receives this data and combines it with other geographical and cartographic data and sends them in turn to the client via the web server. The client, a simple interface finally displays the positions of aircraft on screen.